2015
DOI: 10.1039/c5tb02009c
|View full text |Cite
|
Sign up to set email alerts
|

A conductive stretchable PEDOT–elastomer hybrid with versatile processing and properties

Abstract: Generation of a hybrid PEDOT-elastomer material which retains conductivity upon stretching and is suitable for laser patterning techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…As reported previously [99101], PEDOT coating have a strong beneficial effect on the CSC of metallic microelectrodes, and a significant increase in the CSC was observed following electrodeposition of PEDOT:PTS onto Pt/Ir microelectrodes, from 99.7 ± 17.2 μC mm −2 for bare Pt/Ir microelectrodes to 697.9 ± 23.7 μC mm −2 for pristine PEDOT:PTS coated microelectrodes ( Table 7 ). The incorporation of F6 induced a further significant increase in the CSC of coated Pt/Ir microelectrodes, to a value of 899.5 ± 1.6 μC mm −2 .…”
Section: Methodssupporting
confidence: 81%
“…As reported previously [99101], PEDOT coating have a strong beneficial effect on the CSC of metallic microelectrodes, and a significant increase in the CSC was observed following electrodeposition of PEDOT:PTS onto Pt/Ir microelectrodes, from 99.7 ± 17.2 μC mm −2 for bare Pt/Ir microelectrodes to 697.9 ± 23.7 μC mm −2 for pristine PEDOT:PTS coated microelectrodes ( Table 7 ). The incorporation of F6 induced a further significant increase in the CSC of coated Pt/Ir microelectrodes, to a value of 899.5 ± 1.6 μC mm −2 .…”
Section: Methodssupporting
confidence: 81%
“…The graphene and poly(3,4ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) were also used as conductive components and composited with PGS elastomers to fabricate biodegradable elastic electronic devices. [83,84] Qi et al reported a strategy for judiciously constructing flexible perovskite solar cells (PSCs) based on the PGS elastic substrates. [85] Aliphatic hexamethylene diisocyanate was used as the cross-linking agent to improve the mechanical strength.…”
Section: Polyester Elastomers: Pgsmentioning
confidence: 99%
“…The graphene and poly(3,4‐ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) were also used as conductive components and composited with PGS elastomers to fabricate biodegradable elastic electronic devices. [ 83 , 84 ]…”
Section: Biodegradable Elastic Materials For Electronicsmentioning
confidence: 99%